Assessment of Hydrochemistry and Unconfined Groundwater Quality At East Simeulue Coastal Area, Aceh Province - WISNU ARYA GEMILANG (Badan Geologi, 2019)
East Simulue Subdistrict is one of the areas that has coastal tourism potential that is very good to develop. Tourism development cannot be separated from the provide of tourism facilities and infrastructure, one of which is public infrastructure in the form of providing clean water. Determination of hydrogeochemical characteristics and determination of groundwater quality index (Water Quality Index) is one method of assessing groundwater worthiness in East Simulue. Ground water in the Simulue East coastal area is dominated by HCO3 elements, with a value of Cl / HCO3 ratio <0.5 which indicates that ground water is not affected by sea water, while the Na / Cl ratio> 1 indicates that groundwater has a process of groundwater hydrolysis. There are 6 types of facies hydrochemical facies of East Simulue groundwater, Mg-HCO3, Ca-HCO3, mixing Ca-Na-HCO3, Na-HCO3, Na-SO4 and Ca-SO4, but overall dominated by Mg-HCO3 facies. The ratio of Na ++ K +/ (Na ++ K ++ Ca2 +) as a function of TDS also shows that the chemistry of East Simeulue groundwater is dominated by the interaction of rock (formation) with groundwater. Groundwater quality index classification in Simuelue coastal shows that overall groundwater is in the category of excellent water (good) and good water (good) category.